1999
DOI: 10.1110/ps.8.6.1320
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous folding of a peptide corresponding to the N‐terminal β‐hairpin from ubiquitin

Abstract: The N-terminal 17 residues of ubiquitin have been shown by 1 H NMR to fold autonomously into a b-hairpin structure in aqueous solution. This structure has a specific, native-like register, though side-chain contacts differ in detail from those observed in the intact protein. An autonomously folding hairpin has previously been identified in the case of streptococcal protein G, which is structurally homologous with ubiquitin, but remarkably, the two are not in topologically equivalent positions in the fold. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 46 publications
(31 reference statements)
4
68
0
Order By: Relevance
“…Several experimental and simulation studies have reported sequential folding after the formation of a stable core that includes the strand I-II hairpin and the ␣-helix (36-40). The stability of this N-terminal 1-37 fragment has been investigated by fragmentation studies, multidimensional NMR experiments, and MD simulation (41)(42)(43)(44)(45). MD simulations suggested a transition state with ␤-strands I, II, and V intact and an unfolding pathway involving strands III-V before unfolding of the hydrophobic core (45,46).…”
Section: Resultsmentioning
confidence: 99%
“…Several experimental and simulation studies have reported sequential folding after the formation of a stable core that includes the strand I-II hairpin and the ␣-helix (36-40). The stability of this N-terminal 1-37 fragment has been investigated by fragmentation studies, multidimensional NMR experiments, and MD simulation (41)(42)(43)(44)(45). MD simulations suggested a transition state with ␤-strands I, II, and V intact and an unfolding pathway involving strands III-V before unfolding of the hydrophobic core (45,46).…”
Section: Resultsmentioning
confidence: 99%
“…This finding prompted the investigation of the potential for independent folding of peptide fragments derived from the N-terminus of ubiquitin. Later work showed that a peptide comprising the N-terminal 17 residues of the protein forms a native-like b-hairpin in both aqueous methanol and water, albeit at low apparent population~Cox et al, 1993;Zerella et al, 1999 Hairpin-forming peptides are proving valuable as model systems, but it is important to recognize that they may not be fully representative of b-structures in globular proteins: an isolated hairpin lacks the tertiary interactions that would help to define its geometry in a folded protein. An isolated hairpin may form nonnative intramolecular interactions that will compensate in part for the absence of tertiary interactions.…”
Section: Introductionmentioning
confidence: 99%
“…This finding prompted the investigation of the potential for independent folding of peptide fragments derived from the N-terminus of ubiquitin. Later work showed that a peptide comprising the N-terminal 17 residues of the protein forms a native-like b-hairpin in both aqueous methanol and water, albeit at low apparent population~Cox et al, 1993;Zerella et al, 1999!. Furthermore, protein engineering studies have re-vealed that residues 1-17 are involved in a productive intermediate populated at an early stage of the folding process~Khorasanizadeh et al, 1996!, suggesting that autonomous folding of this structural element might well play an important role in the folding mechanism of this protein.…”
mentioning
confidence: 99%
“…Methods developed to predict the population of a conformer using Nuclear Overhauser Effect (NOE)/ROE intensities or 3 J NH␣ coupling constants often lead to contradictory or unsatisfactory results. 18,19 Such methods typically suffer from the inherent assumption of a two-state equilibrium between the structured conformer and the random coil state. In the peptide studied here, there appear to be at least two-folded conformations.…”
Section: Structure In Denatured State Of ␣-Lactalbuminmentioning
confidence: 99%